Eastern Roman mounted archers and extraordinary medico-surgical interventions at Paliokastro in Thasos Island during the Protobyzantine period : the historical and medical history records and the archaeo-anthropological evidence /: the historical and medical history records and the archaeo-anthropological evidence. (2020) - Agelarakis, Anagnostis P, 1956-
No abstract available